Analisis Tindak Tutur Ilokusi Dalam Rubrik Zodiac Pada Majalah Gadis Edisi 28 Juli - 06 Agustus 2015 - KARTIKAWATI, Enita Ayu (2016)
This study has two objectives. 1) Describe the type of illocutionary acts that appear within the rubric of the zodiac on Girl magazine Issue 28 July to 6 August 2015. 2) Describe the functions of any illocutionary utterances contained in the zodiac rubric Girl magazine Issue 28 July to 6 August 2015. This type of research This includes qualitative descriptive study. The subject of this research is the rubric of the zodiac on Girl magazine Issue 28 July to 6 August 2015. Object of research are aspects of the research subjects who were subjected to research that illocutionary speech acts on the rubric zodiac on Girl magazine Issue 28 July to 6 August 2015. Data collected for this study is a sentence containing illocutionary speech acts on the rubric zodiac on Girl magazine Issue 28 July to 6 August 2015. The source of data in this study a rubric zodiac on Girl magazine Issue 28 July to 6 August 2015. Data collection methods in research This is to consider the method and the method of record. Analysis of the data used in this study is an interactive model.Based on the analysis of research on Analysis of Speech Acts illocutionary In Rubric Zodiac In Magazine Girl Issue 28 July to 6 August 2015, namely: 1) type speech illocutionary which comes in Rubric Zodiac magazine: Girl Issue 28 July to 6 August 2015, include: speech representative, Speech Acts Directives, Expressive Speech Acts and the Declaration Speech Acts. 2) Functions illocutionary utterances anything that appears within the rubric of the zodiac on Girl magazine Issue 28 July to 6 August 2015, consists of two types of competitive functions include requesting and cooperate include announced and reported.